Breast Cancer Is Significantly Associated with Cancers in The First- and Second-Degree Relatives in Ethnic Mizo-Mongoloid Population, Northeast India - Doris Zodinpuii; Jeremy Lalrinsanga Pautu; Bawitlung Zothankima; Lalfakzuala Khenglawt; Doris Lallawmzuali; Rebecca Lalmuanpuii; Lalfak zuali; Lalengkimi Ralte; Rajendra Bose Muthukumaran; Ashok Kumar Varma; John Zothanzama; Nachimuthu Senthil Kumar (Medsci Publications, 2022)
Background: High incidence of breast cancer among the endogamous Mizo-Mongoloid tribe stresses the need to explore the disease pertaining to the family history as well as other risk factors. This study investigates the association of risk factors and inherited diseases with breast cancer. Methodology: The study includes 426 unrelated breast cancer cases and 810 healthy controls of female Mizo ethnicity. Association between reproductive history, lifestyle/ dietary habits, tobacco and alcohol exposures, family history in relation to cancer and inheritable diseases was assessed by univariate logistic regression using Chi-square tests and multivariate analyses using Cox regression. Results: Age at diagnosis was highest between 41 to 50 years. Consumption of fermented pork fat, smoked food and Smoke-less tobacco, lower intake of vegetables/ water, having a first/ or second degree relative with cancers and inheritable diseases were found to be the major risk factors. Certain known factors were also acting as confounding factors. Conclusions: The present study reveals that Mizo women with first- and second-degree relatives of breast cancer, various other cancers and inheritable diseases have increased risk of breast cancer. This study also highlights the importance of analysing genetic factors which can aid in early detection of inherited risk factors.